Comparison of Oral Health-Related Quality of Life, Patient Satisfaction, and Stress Level between Patients Undergone Fixed Orthodontic Treatment and Clear Aligner Therapy - Hhooman Shafaee; Fahimeh Farzanegan; Mostafa Sadeghi; Paria Raeesi; Sajjad Kalateh; Lohrasb Dehghani (Mashhad University of Medical Sciences, 2023)
Introduction: Few studies were conducted on the effectiveness of clear aligners. The present study aimed to compare the quality of life related to oral health, patient satisfaction, and the level of anxiety caused by treatment in patients treated with fixed orthodontics and clear aligners.Materials and Methods: This descriptive-analytical study was conducted on 100 patients undergoing fixed orthodontic treatment six months from the start of their treatment and 100 patients undergoing treatment with clear aligners six months from the start of their treatment. The Oral Health Impact Profile (OHIP-14) questionnaire was used to compare the effect of these two treatments on the quality of life related to the oral health of these patients. Additionally, Patient Satisfaction (PSQ-18) questionnaire was used to check patients' satisfaction and State Trait Anxiety Inventory was used to assess patients' anxiety status.Results: The patients included 78 (38. 8%) males and 122 (61.2%) females. The average quality of life related to oral health was 53.26 with a range of 19 to 69, the average patient satisfaction was 42. 46, with a range of 14 to 50, and the mean and standard deviation of anxiety caused by treatment was 72. 26 ± 13. 93 with a range of 37 to 99. The average anxiety caused by the treatment in the transparent aligners group was significantly higher than the fixed orthodontic group (P<0.001). The average quality of life related to oral health in the transparent aligners group questionnaire was significantly lower than the fixed orthodontic group (P<0.001).Conclusion: The findings of this study showed that the level of anxiety of clear aligners recipients is higher, and their quality of life is lower.